Students’ Error Analysis in Solving Reasoning Problems on Sequences and Series Using Nolting’s Theory - Harini, Elsa; Suanto, Elfis; Hutapea, Nahor Murani (PRISMA, 2025)
Mathematical reasoning ability is an essential competency emphasized in the Merdeka Curriculum, particularly in the Learning Outcomes (CP) for Phase E, which requires students to understand, generalize, and prove mathematical concepts. However, various studies have shown that Indonesian students' mathematical reasoning skills remain relatively low, including in the topic of sequences and series. This study aims to analyze students’ errors in solving mathematical reasoning problems related to sequences and series in Grade 10, based on Nolting’s error theory. The research employed a qualitative descriptive approach involving 20 tenth-grade students from Senior High School 12 Pekanbaru. The research instrument consisted of four mathematical reasoning essay questions covering arithmetic and geometric sequences and series, adapted from Fadillah. The analysis revealed four types of student errors: Careless Errors (34.30%), Connection Errors (31.20%), Test-Taking Errors (21.80%), and Application Errors (17.50%). These errors were attributed to various factors, including cognitive factors such as lack of conceptual understanding and affective factors such as low learning motivation. The findings highlight the importance of teachers in analyzing student errors to help minimize learning difficulties in mathematics and improve the overall quality of mathematics instruction